Best practices in infection prevention and control an international perspective - Soule, Barbara M.; Memish, Ziad A.; Malani, Preeti N.; IG Publishing (Oak Brook, Il. Joint Commission International, 2012)
An infection prevention and control (IPC) resource for health care organizations. It provides thorough analysis of Joint Commission International (JCI) infection prevention and control requirements, as well as case studies, tips, and tools for increasing IPC compliance and patient safety.
Infection prevention and control a global perspective on a health care crisis -- Joint Commission International's infection prevention and control standards and requirements: a detailed study -- Surveying infection prevention and control -- Developing an effective infection prevention and control program: challenges, tips, and tools for success -- Maintaining an effective infection prevention and control program: more challenges, tips, and tools -- Lessons learned: the 2003 Hong Kong and Toronto SARS outbreaks.
Electronic reproduction.
Keywords: Communicable diseases -- Prevention -- Handbooks, manuals, etc; Infection -- Prevention -- Handbooks, manuals, etc; Public health -- International cooperation; Electronic books